Generative AI, Deepfake, dan Hak Cipta di Indonesia dalam Tinjauan Yuridis - Ida Ayu Putu Anggie Sinthiya; Ricco Herdiyan Saputra (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
The rapid advancement of Generative AI has created legal vacuums regarding Deepfake content and copyright infringement. This research aims to analyze the legal status of AI and the distribution of liability between users and developers. Utilizing socio-legal methods with qualitative data analysis via NVivo 12, this study involves informants from law enforcement and academia in Lampung. The results indicate that AI currently remains a legal object, yet requires the implementation of Digital Hybrid Liability Theory to map fault proportionally between User intent and system negligence. It is suggested that the Indonesian Government immediately formulate specific AI governance regulations mandating digital watermarking to ensure information transparency and protect human dignity without hindering technological innovation.